Analysis of Oil-Water Distribution Law and Main Controlling Factors of Meandering River Facies Reservoir Based on the Single Sand Body: A Case Study from the Yan 932 Layer of Y Oil Area in Dingbian, Ordos Basin - Tiaotiao Shi; Shengping He; Kaitao Yuan; Mingjun Liu; Min Wang; Xingping Tu; Liwen Chang (Geofluids)
After the oilfield development enters the medium and high water cut stage, the fine three-dimensional description of the single sand body, the distribution rules of the remaining oil, and its main controlling factors have become the focus of research. The premise is to understand the original oil and water distribution characteristics and the important influencing factors of the reservoir. Taking the Yan 932 reservoir of Y oil area in Dingbian as an example, combined with the meandering river sedimentary model, this paper uses dense well pattern logging data to dissect single sand body on the foundation of the core and logging results. The conclusion shows that, first, Yan 932 layer is divided into two stages: Yan 932-1 and Yan 932-2, which constitute four single sand body superposition configuration modes, namely, type I, type II, type I & II, and type I/II. Second, type I & II is mainly developed in the sand body of the main channel. In the west of the main channel sand body, type I, type II, and type I/II are developed. Only type II is developed in the east of the main channel sand body. Thirdly, sedimentary microfacies, sand body thickness, sand body configuration, and structural characteristics are the key factors influencing the oil-water distribution law of the Yan 932 reservoir.